A61 COLORECTAL ANASTOMOTIC VARICES IN A PATIENT WITH PORTAL HYPERTENSION: A CASE REPORT AND REVIEW OF THE LITERATURE. (1st March 2018) - Sasson, G; Yong, E; Steinhart, H
Abstract: Background: Ectopic varices (EV) account for 5% of variceal bleeding. Anastomotic varices (AV) are a rare form of EV that have been predominantly described in small bowel. To our knowledge colorectal AV have not been described. We describe a case of colorectal AV hemorrhage in a patient with portal hypertension (PH) treated with endoscopic band ligation (EBL). Aims: To gain insight into the incidence, location and optimal treatment of AV. Methods: Case report and literature review. Results: Case report: A 63 year old woman with alcoholic cirrhosis presented with recurrent lower GI bleeding (LGIB) 2 years following sigmoid resection and primary colorectal anastomosis for colorectal cancer. Colonoscopy demonstrated anastomotic neovascularization with prominent submucosal vessels suggestive of varices, without high risk stigmata. Her symptoms resolved without intervention. She returned 5 weeks later with recurrent LGIB; sigmoidoscopy revealed AV with stigmata of recent hemorrhage successfully managed with single EBL. The next episode of LGIB occurred over 2 years later; colonoscopy revealed AV with visible erosions treated with EBL. She attended subsequent EBL sessions until variceal extinction. After several months, she presented on 3 occasions over a 2-month period for LGIB in the context of alcohol binges. AV with erosions were visualized at each episode, however there was no active bleeding or endoscopic intervention. Literature review: A PubMed and Cochrane Database of Systematic Reviews search produced publications describing varices at surgical sites, most of which were peristomal. There were 4 cases of esophagojejunal AV, 13 cases of gastroduodenal AV, and 3 cases of jejunal varices after hepatico- or choledochojejunostomy. The most distal anastomosis reported was a case series of 10 patients with PH who underwent ileal pouch-anal anastomosis; none developed pouch variceal bleeding. The lack of colonic variceal involvement, particularly of the descending and sigmoid colon, may relate to their anatomical distance from, and indirect drainage to, the portal vein, resulting in indirect transmission of venous pressure. Management of AV is controversial. Endoscopic intervention with N-butyl-2-cyanoacrylate is efficacious in small bowel AV. Transjugular intrahepatic portosystemic shunt and percutaneous transhepatic obliteration is beneficial in EV. Surgical resection or transcatheter embolization can be effective, however perioperative morbidity and mortality is high. To our knowledge, EBL for colorectal AV has not been described. This treatment modality appears to be useful for temporary hemostasis but rebleeding rates appear to be high. Conclusions: A case report of colorectal AV is presented. EBL achieved temporary hemostasis but rebleeding rates were high. Funding Agencies: None